Application of carbon monoxide for treatment of acute kidney injury - Nakao, Atsunori (Acute Med Surg, 2014)
Acute kidney injury in critically ill patients is common and associated with a substantial increase in morbidity and mortality. Even with aggressive medical care and renal replacement therapy, acute kidney injury remains a significant health care concern. Recent published reports offer new strategies for the prevention and amelioration of acute kidney injury using carbon monoxide. Although considered a toxic environmental gas, carbon monoxide has recently aroused scientific and clinical interest, as its beneficial effects and mechanisms of action have been substantially defined in various in vitro and in vivo experiments. The exogenous application of carbon monoxide can confer cytoprotection by modulating intracellular signaling pathways through its anti‐inflammatory, anti‐apoptotic, vasodilative, antithrombotic and antiproliferative properties. Thus, evidence is accumulating to support the notion of carbon monoxide treatment for acute kidney disease. In this review, we focus on the extensively analyzed advantageous value of treatment with inhaled/soluble carbon monoxide in the context of kidney injury. Mechanisms such as signaling pathways, as well as an expanded view regarding toxicity and side‐effects, are described broadly. In addition, we discuss the clinical applicability of carbon monoxide as a promising therapeutic strategy for the treatment of patients with acute kidney disease based on translating basic experimental findings into clinical application.